2015
DOI: 10.1007/s00423-015-1315-x
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and ghrelin levels after laparoscopic Nissen fundoplication

Abstract: Total plication of the fundus impairs its ghrelin-secreting functions for up to 4 weeks and is accompanied by weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…One study observed that the concentration of ghrelin increased significantly after gastric banding operation ( P = 0.01) and Nissen fundoplication ( P = 0.02), but it decreased significantly after RYGB operation ( P < 0.001), which may be related to the complete preservation of the fundoplication in Nissen [ 32 ]. However, another study found that BMI and ghrelin decreased in the first week and the fourth week after Nissen fundoplication, and there was a strong correlation between ghrelin value and BMI change in the fourth week after operation, probably because fundoplication would damage the secretion function of ghrelin in the gastric fundus [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study observed that the concentration of ghrelin increased significantly after gastric banding operation ( P = 0.01) and Nissen fundoplication ( P = 0.02), but it decreased significantly after RYGB operation ( P < 0.001), which may be related to the complete preservation of the fundoplication in Nissen [ 32 ]. However, another study found that BMI and ghrelin decreased in the first week and the fourth week after Nissen fundoplication, and there was a strong correlation between ghrelin value and BMI change in the fourth week after operation, probably because fundoplication would damage the secretion function of ghrelin in the gastric fundus [ 33 ].…”
Section: Discussionmentioning
confidence: 99%